Neanderthals in the Rain: Assessing Neanderthals' Strategies to Survive Wet and Cold Environments through an Experimental Analysis - Eleonora Scandola; Penny Spikins (EXARC Journal)
Neanderthals' adaptations to cold climates have been extensively debated, however, limited attention has been given to their survival in cold and wet environments. These conditions increase the dangers of cold-induced injuries such as frostbite or hypothermia, as wet clothing loses its insulative capacities. This research explores whether and how Neanderthals faced such changes and their implications on activities and behaviours. After reviewing biological and cultural adaptations and behaviours, this thesis devises experimental strategies to waterproof clothing. These experiments, inspired by ethnographic accounts, utilise Neanderthals' technological repertoire. The results revealed that the most successful strategy required significant effort to be produced. Evidence suggests Neanderthals tended to remain isolated in their territories and cover shorter distances in their lifespan. Larger group numbers and greater interconnectivity could have supported job division and promoted technological complexity. Therefore, the challenges posed by cold and wet environments may have constrained Neanderthals' territorial expansion, reducing group sizes and limiting social networks. Simultaneously, their restricted interconnectivity could have hindered the development of complex successful strategies, further limiting Neanderthals’ ability to cope with wet and cold conditions. This research calls for a deeper, more focused understanding of environmental adaptations and proposes a framework to unravel the tangled relationships between environment, behaviours and technology.